2017
DOI: 10.2135/cropsci2016.06.0492
|View full text |Cite
|
Sign up to set email alerts
|

Best Management Practices Effects on Anthracnose Disease of Annual Bluegrass

Abstract: Increased N fertilization, mowing height, and sand topdressing are management practices that can suppress anthracnose disease of annual bluegrass [Poa annua L. f. reptans (Hausskn) T. Koyama; ABG] caused by Colletotrichum cereale Manns. A 3‐yr field study evaluated the relative importance and interactions of these factors on anthracnose severity, turfgrass quality, and ball roll distance (BRD) on ABG turf in North Brunswick, NJ. A factorial combination of mowing height (2.3 and 3.2 mm), N fertilization (100 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…However, topdressing alone is not sufficient for controlling anthracnose disease. Hempfling et al (2017) reported topdressing in combination with other best management practices without fungicides provided acceptable disease suppression during moderate but not severe disease epidemics.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, topdressing alone is not sufficient for controlling anthracnose disease. Hempfling et al (2017) reported topdressing in combination with other best management practices without fungicides provided acceptable disease suppression during moderate but not severe disease epidemics.…”
Section: Discussionmentioning
confidence: 98%
“…Anthracnose is particularly severe on annual bluegrass [Poa annua L. f. reptans (Hausskn) T. Koyama] putting greens (Smiley et al, 2005). Sand topdressing programs can improve turf quality and suppress the severity of anthracnose on annual bluegrass putting green turf (Hempfling et al, 2015(Hempfling et al, , 2017Inguagiato et al, 2012Inguagiato et al, , 2013Roberts and Murphy, 2014;Wang et al, 2018). Inguagiato et al (2013) found that particle shape of topdressing sand had no effect on anthracnose.…”
mentioning
confidence: 99%
“…Values followed by the same lowercase letter are not significantly different according to LSD (0. (Hempfling, Clarke, & Murphy, 2015, 2017Inguagiato et al, 2008Inguagiato et al, , 2009Inguagiato et al, , 2012Inguagiato et al, , 2013Towers, Green, Weibel, Majumdar, & Clarke, 2003).…”
Section: Field Maintenancementioning
confidence: 99%
“…Grooming (1.3-mm depth, 1.5-mm blade width, 5-mm lateral blade spacing), verticutting (3.8-mm depth, 1.5-mm blade width, 10-mm lateral blade spacing), scarifying (7.6-mm depth, 1.5-mm blade width, 40-mm lateral blade spacing), and solid-tining (57-mm depth, 6-mm tine width, 38-by 38-mm spacing) were applied on 24 July and 14 August 2009 and 2 June, 23 June, and 19 July 2010. Weekly grooming was applied every (Hempfling, Clarke, & Murphy, 2015, 2017Inguagiato et al, 2008Inguagiato et al, , 2009Inguagiato et al, , 2012Inguagiato et al, , 2013Towers, Green, Weibel, Majumdar, & Clarke, 2003).…”
Section: Field Maintenancementioning
confidence: 99%
“…Benn.) incidence by 50% (Green, 2015), and the severity of anthracnose ( Colletotrichum cereale Manns graminicola ) for longer periods (Hempfling et al, 2017). Compacting snow is a practice that may lower the air temperature at the snow–soil interface below freezing and prevent certain snow molds from developing (Blunt and Tisserat, 2007).…”
Section: Useful Conversionsmentioning
confidence: 99%